BASSILO - Battery storage sizing and location in distribution systems - Tiago João Amorim Abreu (2019)
This thesis addresses the problem of sizing and optimal location of non-domestic energy storage, batteries, in distribution networks that integrate distributed photovoltaic generation, with the objective of analysing its exploration potential in the energy business. For this purpose, a formulation based on line programming and the EPSO metaheuristic (Evolutionary Particle Swarm Operation) has been proposed for the minimization of the costs of including a storage system in the energy grid.Given the size and location of the battery, a formulation based on linear programming will allow to determine the optimal operation of the battery for the following cases: in the first study, the operation of the battery in the base of one day. In the second, the operation of the battery in the base of multiple consecutive days. The optimal size and location of the battery is determined using the EPSO metaheuristics, which will evaluate the costs involved in the two perspectives of operation of the battery, previously proposed.The results presented are for a realistic power network, CIGRE - European MV distribution network benchmark, modified to be operated as a radial network, comprising distributed loads (commercial and residential) and photovoltaic generation for several operating scenarios in which the variation of energy prices, are considered to validate the proposed business exploration model.